H.K. Corning diaries - Corning, H. K.
Diaries pertaining to Corning's business and personal affairs and to political matters. Subjects include the establishment of the Japanese embassy in the U.S., the secession of South Carolina, Abraham Lincoln's presidency and assassination, and the Civil War. Newspaper clippings interspersed throughout the diaries.
Commission agent of New York, N.Y.
Collection material in English.
Keywords: Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865 -- Assassination; Japan. -- Taishikan (U.S.); Secession -- South Carolina; Japan -- Foreign relations -- United States; New York (N.Y.) -- Commerce; South Carolina -- Politics and government -- 1775-1865.; United States -- Foreign relations -- Japan; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 1861-1865.; Commission agents